Combating Money Laundering and Terrorist Financing - Stefan Haigner; Friedrich Schneider; Florian Wakolbinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
International policy standards in the fight against money laundering and terrorist financing are set forth by the Financial Action Task Force (FATF) recommendations on Anti-money laundering (AML)/Combating the financing of terrorism (CFT) policies. While those standards are very high and require, for example, financial businesses to strictly pursue the "know your customer principle", countries compliance with the standards is low. In putting efforts in increasing compliance and harmonizing enforcement, however, the costs (both in terms of resources as well as reduced privacy rights) have to be taken into account.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: 330